Catalytic behaviour of metallophthalocyanines towards the detection of nitric oxide - Vilakazi, Lea Sibulelo (Rhodes University, Faculty of Science, Department of Chemistry, 2002)
Electrocatalytic reduction and oxidation of nitric oxide (NO) using cobalt phthalocyanine complexes have been studied and compared to vitamin Bâ‚ â‚‚ and other metallophthalocyanine (MPc) complexes. Modifying a glassy carbon electrode with these complexes resulted in improved sensitivity of the electrode allowing detection of NO to 10â »â ¹ mol dmâ »Â³. The mechanisms of catalysis were studied. Electrocatalysis of NO involves coordination of NO to the MPc complex. Hence catalytic activity is affected by the nature of the metal center. However coordination of NO to the MPc complex has to be reversible to eliminate poisoning of the electrode. Though FePc gave the best sensitivity and lowered the reduction potential more than CoPc, the strong Fe-NO bond resulted in the poisoning of the electrode hence, rendering the electrode unstable. Rate constants for NO coordination to the MPc complexes were studied. These rates were smaller than the studied NO porphyrin coordination rates. Electrocatalytic reduction of NO using MPc complexes involves a transfer of an electron from the metal center to the NO ligand. Hence, substitution of electron-donating grohps on the cobalt pthalocyanine complex resulted in improved sensitivity and catalytic activity. A CoPc modified microelectrode (11Î¼m) was used to monitor NO in human blood components and to detect NO in a rat brain. Detections of NO were also done in aqueous solutions in the presence of interfering species such as dopamine and serotonin. An interaction between NO and serotonin was observed.
Keywords: Electrochemistry; Nitric oxide